Evaluation of extended and continuous use oral contraceptives - Kristen Page Wright; Julia V Johnson (Dove Medical Press, 2008)
Kristen Page Wright, Julia V JohnsonUniversity of Vermont College of Medicine and Reproductive Endocrinology and Infertility, Women’s Health Care Services, Fletcher Allen Health Care, Burlington, VT USAAbstract: Oral contraceptives are classically given in a cyclic manner with 21 days of active pills followed by 7 days of placebo. In the past 4 years, new oral contraceptives have been introduced which either shorten the placebo time, lengthen the active pills (extended cycle), or provide active pills every day (continuous). These concepts are not new; extended and continuous pills were first studied in the 1960s and 1970s and have been provided in an off-label manner by gynecologists to treat menstrual disorders, such as menorrhagia and dysmenorrhea, and gynecologic disorders, such as endometriosis. Now that extended and continuous combined oral contraceptives are available for all patients, it is critical for providers to understand the physiology, dosing, side effects, and benefits of this form of oral contraceptive. This article reviews the history and the potential uses of the new continuous combined oral contraceptive.Keywords: oral contraceptives, administration, dosage, adverse effects, menstrual disturbances